The Evolution And Development Of Global Translation Studies - Bobokulova, Gulruh Sharipovna (TLEP – International Journal of Multidiscipline, 2026)
This article scientifically analyzes the formation and development stages of global translation studies as a distinct discipline. The research highlights the transition of translation from traditional linguistic approaches to modern cultural, cognitive, and technological paradigms. Furthermore, the role of significant schools in world translation studies, particularly the manipulation school, skopos theory, and contemporary trends such as artificial intelligence and machine translation, is examined. The purpose of the article is to reveal the unique evolution of translation studies as an independent science and its interdisciplinary connections.